Perspectives Matter: Insecure Residency Status Accounts for Aggressive Emotions in Adolescent Refugees - Lara L. Eder; Alexandra Martin; Gerhard Hapfelmeier; Marco Walg (MDPI AG, 2024)
Unaccompanied refugees are a high-risk group for trauma-induced psychiatric disorders. Besides traumatic experiences pre- and during migration, post-migration stressors such as insecure residency status affect refugees' mental health and foster aggressive emotions. High levels of psychological distress and psychopathology distort time perspectives. Consequently, an insecure residency status linked to distress may influence a refugee's time perspective. This study investigated psychological distress, PTSD symptoms, aggressive emotions, and time perspectives in 33 unaccompanied adolescent refugees with and without secure residency status in Germany. Refugees with precarious residency status showed higher levels of overall distress and aggression than individuals with secure residency status. Both groups revealed a distorted time perspective profile, but individuals with a residence permit showed a stronger orientation toward the present hedonistic perspective than those without a permit. Higher aggressive emotions were related to insecure status, higher levels of psychological distress, more pronounced PTSD symptoms, and lower orientation to future time perspective. Distorted time perspectives among refugees may be caused by traumatic experiences and having been uprooted, independently of their residency status in the host country. A higher future orientation may buffer the association between distorted time perspectives and aggressive emotions in the highly stressed group of unaccompanied adolescent refugees.